Transformation of Pesantren in Maintaining Good Character - Muhammad Hifdil Islam; Abd Aziz (Institut Ilmu Keislaman Zainul Hasan Genggong, 2020)
Education is the main pillar of nation building. The success of a nation’s education is closely related to the progress achieved. Because it is a necessity, so the government and society should prioritize the overall development of the field of education. Especially education that shapes the national character of the nation. Pesantren as one of the indigenous Indonesian National Education sub-systems, has special advantages and characteristics in applying character education for their students (santri). The writing method this article is writer takes some of schoolars argument that related with the topic of this articel.“this article try to highlight the pesantren as the root of history of islamic education in Indonesia, the transformation of pesantren education system and the role of pesantren in Indonesia in maintaining the good character of student. And the result of this article show that pesantren has many types of system and it has a big role in maintaining the good character of student.